The Effect of Using Animation Movie on Students' Writing Skill of Narrative Text at Tenth Grade Students of SMA Negeri 3 Pematangsiantar - Layola Veronika Naibaho; Partohap Saut Raja Sihombing; David Togi Hutahaean (International Journal of Technology and Education Research, 2026)
This research was conducted based on the problems found in English learning, especially in writing skills. This research used a quantitative method with a quasi-experimental design. The population of this research was the tenth grade students of SMA Negeri 3 Pematangsiantar, consisting of 76 students. The sample of this research consisted of two classes: class X-3 as the experimental class and class X-4 as the control class, with 25 students in each class. The instrument used in collecting the data was a writing test in the form of pre-test and post-test. The data were analyzed by using SPSS version 24.0 through paired sample t-test and independent sample t-test. The result of the research showed that the students in the experimental class had better improvement than the students in the control class. The mean score of the experimental class increased from 62.44 in the pre-test to 79.28 in the post-test, while the control class increased from 65.96 to 72.68. The result of the independent sample t-test showed that the significance value (Sig. 2-tailed) was lower than 0.05, which indicated that the alternative hypothesis (Ha) was accepted and the null hypothesis (Ho) was rejected. In addition, the effect size was categorized as a large effect. Therefore, it can be concluded that the use of animation movies gave a significant effect on students’ writing skill of narrative text at the tenth grade students of SMA Negeri 3 Pematangsiantar.